New natural fibre reinforced composite brake friction material - Maleque, Md. Abdul; A., Atiqah; R. J., Talib; Halim, Zahurin (2011)
This paper presents a new formulation of free asbestos brake friction materials with a view to replace the use of asbestos whose dust is carcinogenic and has a harmful effect to the human being. Five different laboratory formulations (such as, S1, S2, S3, S4 and S5) were selected with varying coir fiber contents from 0, 5, 10, 15, and 20 volume fraction along with binder, friction modifiers, abrasive material and solid lubricant using powder metallurgy technique for the development of new natural fibre reinforced brake friction materials. The properties examined are density, porosity, microstructural analysis, hardness and compressive strength using densometer, SEM, hardness tester and universal testing machine. The better properties in terms of higher density, lower porosity and higher compressive strength were obtained from S2 and S3 samples. The microstructure reveals uniform distribution of resin in the coir fiber in S2, S3 and S4. It can be concluded that S2 and S3 showed better physico-mechanical properties compared to other formulations. Hence, natural coir fiber can be used as a candidate fiber or filler material for the mass-scale fabrication of asbestos-free brake pad without any harmful effect. Keywords: natural fiber, friction material, Density, Hardness, Compressive Strength and Microstructure.